Effects of Morphology and Topology on the Effective Stiffness of Chiral Cellular Materials in the Transverse Plane - Alp Karakoç; Ertuǧrul Taciroǧlu (Advances in Materials Science and Engineering)
The present study investigates the influence of topology and morphology on the effective stiffness of chiral cellular materials in the transverse plane by means of a homogenization method. For this purpose, finite element models of representative volume elements for regular hexagonal and hexagonal-chiral configurations are used and simulations are conducted to quantify how cell topology—that is, chirality inside the cell—and cell wall slenderness affect the effective stiffness. Closed form solutions for regular hexagonal square and triangular RVEs provided in the literature are then taken as a basis for model validation. The results indicate that there are drastic differences between regular hexagonal and hexagonal-chiral configurations, which can be explained in terms of deformation mechanism transformations between bending and stretching. The investigations also reveal the positive impact of cell wall slenderness on stiffness due to volumetric increase in the cell wall material resisting the deformation.